أدويسا التنوع الثقافي وصراع الحضارات - مقاربات في أنثروبولوجيا التفسير الثقافي – (Numerus academy review, 2026)
Anthropological research takes its striking vitality from that plurality / diversitythat characterizes the human cultural system; renewed diversity according to the coordinates of time and space, where cultural manifestations vary from one group to another, according to an innate system of difference framing human tendencies moral / belief and behavioral, but the anthropological research was not To do so - as a cognitive orientation that seeks to reveal the existential elements of the other / different - otherwisethe diversity obtained at the level of social and cultural performances. Thus, research in the system of "difference" and "differentiation / differentiation" is the characteristic bywhich the understanding of the "other" is established, as it is the diversity that embodies the image of human existence in its religious, linguistic, ethnic and other aspects.